Employer Responsiveness to Online Reviews: A Signal of Caring About Employees - Christoph E. Höllig; Endrit Ademi; Andranik Tumasjan (Human Resource Management, 2025)
Employer reviews (i.e., online workplace ratings authored by employees) attract broad interest and shape the opinions of potential employees. Thus, companies face the challenge of dealing with these workplace judgments that are outside their direct control. While prevailing theoretical perspectives suggest that responding to third-party judgments may be an effective way for companies to deal with them, they focus on responses to negative judgments that threaten companies' reputations. Based on signaling theory, we argue that employer responsiveness, signaled by an employer's first response to an employer review, serves as a mechanism of indirect control over employer reviews. Applying a difference-in-differences approach—a statistical technique to estimate the causal effect of the treatment (i.e., responsiveness) by comparing it to a control group without the treatment—on a sample of 298,269 reviews of 21,099 employers over 45 quarters posted on the employer review website Kununu, we hypothesize and find that compared to nonresponsive employers, responsive employers receive more diverse (i.e., variety of topics covered) and extensive (i.e., amount of information provided) employer reviews. These effects are especially pronounced in the case of negative employer reviews. Our findings can serve as a guide for employers in dealing with third-party judgments by demonstrating that employer responsiveness is a valuable signal enhancing online review quality. We contribute to the growing body of HRM research on employer reputation on social media, a critical factor influencing recruitment and retention outcomes. Our study opens new avenues for research to explore the role of responsiveness as a strategic signal in employer brand management.
Keywords: 650